2012
DOI: 10.1371/journal.pone.0044053
|View full text |Cite
|
Sign up to set email alerts
|

Meal Time Shift Disturbs Circadian Rhythmicity along with Metabolic and Behavioral Alterations in Mice

Abstract: In modern society, growing numbers of people are engaged in various forms of shift works or trans-meridian travels. Such circadian misalignment is known to disturb endogenous diurnal rhythms, which may lead to harmful physiological consequences including metabolic syndrome, obesity, cancer, cardiovascular disorders, and gastric disorders as well as other physical and mental disorders. However, the precise mechanism(s) underlying these changes are yet unclear. The present work, therefore examined the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 57 publications
3
51
0
3
Order By: Relevance
“…The present study showed the effects of lifestyle alterations on biological activity by means of microminipigs. In rodents, a high-fat diet has been reported to increase LA and BT during inactive (lights on) periods (32,33). However, we should consider the dietary habits and behaviors of the respective animals when evaluating the effects of dietary and lighting conditions.…”
Section: Measurement Of La and Btmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed the effects of lifestyle alterations on biological activity by means of microminipigs. In rodents, a high-fat diet has been reported to increase LA and BT during inactive (lights on) periods (32,33). However, we should consider the dietary habits and behaviors of the respective animals when evaluating the effects of dietary and lighting conditions.…”
Section: Measurement Of La and Btmentioning
confidence: 99%
“…Increased BT during the nocturnal period due to delayed mealtime may account for diet-induced thermogenesis (33). The increased LA and BT during nocturnal periods under the MHF dietary conditions may have been induced by the increased energy intake (about 0.8 kcal/g of diet) or gastrointestinal signals produced by the increased intake of the lard and cholesterol (34).…”
Section: The Effects Of a Moderately High-fat Diet And Lighting On mentioning
confidence: 99%
“…A series of interesting experiments demonstrated that circadian reprogramming via time restricted feeding (controlling access to food without calorie restriction) led to re-setting of metabolic rhythms, and impacted tumor growth (Li et al, 2010), reversed liver-specific abnormalities (Maywood et al, 2010), or impacted obesity onset (Hatori et al, 2012). Shift-work, also associated with disrupted sleep and feeding patterns, is now widely accepted as a disease pre-disposition factor (Barclay et al, 2012; Yoon et al, 2012). Well-established are also the links between sleep disruption and immunity (Besedovsky et al, 2012) as well as the daily (Smolensky et al, 2015) and seasonal patterns of inflammation and chronic inflammatory diseases (Dopico et al, 2015; Iikuni et al, 2007; V.…”
Section: Towards Integrative Models In Systems Biology and Systemsmentioning
confidence: 99%
“…It has been shown that timing of access to food, effectively setting metabolic rhythms, impacts tumor growth (Li et al 2010), reverses the liver-specific abnormalities in a model of Huntington's disease (Maywood et al 2010), alters high-fat diet metabolism impacting obesity factors (Hatori et al 2012). On the other end, shift-work, often associated with disrupted feeding patterns, is a known disease pre-disposition factor (Yoon et al 2012; Barclay et al 2012). Similarly well-established are the links between sleep disruption and immunity (Besedovsky et al 2012) whereas the daily (Smolensky et al 2015) and seasonal patterns of inflammation and chronic inflammatory diseases (Dopico et al 2015; Iikuni et al 2007; Kumar et al 2007) are well established.…”
Section: Qsp: the Contextmentioning
confidence: 99%